Use of perfluorocarbon liquids in proliferative vitreoretinopathy: results and complications. - Stolba, U (1995)
BACKGROUND--The present study was set up to evaluate the influence of perfluorocarbon liquids on the postoperative anatomical and functional results as well as on the complication rates in eyes with proliferative vitreoretinopathy (PVR). METHODS--Sixty five consecutive eyes (64 patients) with PVR in different stages requiring surgical intervention where liquid perfluorocarbons were used were compared with 64 consecutive eyes (62 patients) operated without the help of perfluorocarbon immediately before this time. Both groups were similar with regard to severity of PVR, number of operations, and initial visual acuity. The observation period was shorter in the perfluorocarbon group because they were operated more recently (17.4 months as against 24.4 months). RESULTS--The anatomical as well as the functional success rates were not significantly higher in the perfluorocarbon group (69% v 61% and 65% v 53% respectively). However, in cases operated on without perfluorocarbons where reproliferation would occur it was of much greater severity than in cases where perfluorocarbons were used. The number of uncured cases with contraction of the retina at least in the inferior half was more than twice as high in the group operated on without perfluorocarbon. Combined with massive reproliferation secondary glaucoma and bullous or band keratopathy were more frequent in eyes treated before the use of perfluorocarbon. CONCLUSION--The intraoperative use of perfluorocarbon liquids in vitreoretinal surgery does not prevent postoperative reproliferation but does reduce its severity.